The Seven Years War and the old regime in France : the economic and financial toll - Riley, James C. (Princeton legacy library, 1986)
Taking French participation in the Seven Years War as a case study, this book examines the effects of war on the economy and on government finance, finding that the economic toll has usually been exaggerated and the financial toll seriously underestimated. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.